Lung Abscess with a Refractory Bronchopleural Fistula Saved from Potentially Fatal Sepsis by Omentoplasty and Extracorporeal Membrane Oxygenation - Jumpei Takamatsu; Jinkoo Kang; Aya Fukuhara; Yuichi Yasue; Sae Kawata (Case Reports in Critical Care)
Controlling air leaks during thoracic drainage in patients with lung abscesses caused by bronchopleural fistulas is challenging. To reduce the occurrence of air leaks, positive pressure ventilation should be avoided whenever possible. A 69-year-old man presented with a 10-day history of gradually worsening chest pain. He had lost consciousness and was brought to the emergency room. His SpO2 was approximately 70%, and his systolic blood pressure was approximately 60 mmHg. Chest radiography and computed tomography revealed findings suggestive of a right pyothorax. Therefore, thoracic drainage was performed. However, the patient’s respiratory status did not improve, and his circulatory status could not be maintained. Therefore, extracorporeal membrane oxygenation was introduced after the improvement in circulation by noradrenaline and fluid resuscitation, resulting in adequate oxygenation and ventilation without the use of high-pressure ventilator settings. Subsequently, omentoplasty for a refractory bronchopleural fistula was successfully performed, and the air leak was cured without recurrence of the lung abscess.